1979
DOI: 10.1128/iai.23.2.347-352.1979
|View full text |Cite
|
Sign up to set email alerts
|

Cell-mediated immune response to bacterial products in human tonsils and peripheral blood lymphocytes

Abstract: Lymphoproliferative responses of tonsillar tissue lymphocytes and peripheral blood lymphocytes to phytohemagglutinin and specific bacterial product antigens were studied in children undergoing tonsillectomy and adenoidectomy. Tonsillar tissue lymphocytes responded to optimal concentrations of phytohemagglutinin. Varidase, and streptolysin-O in a manner similar to peripheral blood lymphocytes. Higher base-line mitogenic activity in tonsillar lymphocytes was frequently associated with the presence of Staphylococ… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
4
1

Citation Types

0
6
1

Year Published

1981
1981
2007
2007

Publication Types

Select...
10

Relationship

0
10

Authors

Journals

citations
Cited by 27 publications
(7 citation statements)
references
References 17 publications
0
6
1
Order By: Relevance
“…There is no appropriate animal model of meningococcal colonization currently available and both mucosal lymphoid organization and regulatory responses differ between rodent and human systems. We have therefore used human PT, a frequent location for meningococcal carriage and a likely site of immune induction (Drucker et al, 1979;Brandtzaeg et al, 1997), to investigate the cellular immune response to meningococcal antigens. We show that maturation of mucosal immunity to the meningococcus is characterized by the emergence of predominantly pro-inflammatory CD4 + CD45RO + memory T cells, controlled by cells with a GITR-regulatable CD4 + CD25 + phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…There is no appropriate animal model of meningococcal colonization currently available and both mucosal lymphoid organization and regulatory responses differ between rodent and human systems. We have therefore used human PT, a frequent location for meningococcal carriage and a likely site of immune induction (Drucker et al, 1979;Brandtzaeg et al, 1997), to investigate the cellular immune response to meningococcal antigens. We show that maturation of mucosal immunity to the meningococcus is characterized by the emergence of predominantly pro-inflammatory CD4 + CD45RO + memory T cells, controlled by cells with a GITR-regulatable CD4 + CD25 + phenotype.…”
Section: Discussionmentioning
confidence: 99%
“…The mechanism of infectious influence is not yet clear. The assumption is that lymphocytes from diseased tonsils could be refractory or tolerant to these bacterial activators showing less degree of proliferation on stimulation with dominant bacterial antigens than healthy one (18,19). The problem of investigator is the fact that healthy tonsils could be hardly defined.…”
Section: Discussionmentioning
confidence: 99%
“…immunization led to increased ASC responses associated with enlarged ASC precursor frequencies in a previously primed tonsil compared with those of a not previously injected tonsil. Previous studies have shown that tonsillar MNC can be induced to proliferate and differentiate into ASCs upon in vitro exposure to antigens normally encountered in the upper respiratory tract but not elsewhere (6,14,18,21). The results of this study confirm that tonsils can support the development of immunological memory and further indicate that such development is highly dependent on local antigen exposure.…”
Section: Discussionmentioning
confidence: 99%